Estudio del funcionamiento de los puntos wifi de la ciudad de Latacunga - Osorio Fajardo, Dayana Estefanía (2019)
This research project shows the state of the Wi-Fi networks offered by the “GADL” for free, in which a network audit is carried out on the seven internet access points that are the most relevant in the urban area of the city. Different techniques, methodologies, and tools that also serve for the development of this research were used. To get the results, the researchers use the Wifislax application which is a GNU Linux distribution; by this, it was possible to verify the vulnerabilities and deficiencies of each of them; the aspects that were audited were: signal, channel, security, quality, provider and the protocol that are used. By gathering this information, it was clear that no networks have security and privacy protocols, as well as the wrong location of the AP so, the signal is not good which it is a significant aspect of the lack of Internet access. Looking for a way to optimize the needs found, a scheme was proposed, where essential points to correct in order to provide an effective and quality service for the entire community of Latacunga city are recommended.